BUT IS IT ‘AUGMENTED REALITY’? BOUNDARY WORK OVER THE NAMING, DEFINITION, AND CATEGORIZATION OF AN EMERGING INFORMATION TECHNOLOGY - Liao, Tony (AoIR Selected Papers of Internet Research, 2015)
This article is based on over three years of fieldwork and participation observation in the AR community. Participant observation is particularly useful when the research examines interactions that take place in specific, physical locations (Lofland et al. 2006), and there were several places where the AR industry gathered – industry conferences, standards meetings, and academic conferences. From 2011-2014, I attended industry conferences in San Francisco, London, Munich, and New York, academic conferences in Atlanta and Adelaide, and standards conferences in New York, Barcelona, Rome, Redlands, and Crystal City. I attended over 12 conferences spanning 6 different countries. I supplemented this with 48 in-depth interviews with leaders in the community.